Esophageal Varices in Pakistani Cirrhotics High Prevalence, Strong Predictors, and the Role of Non-Invasive Screening in Resource-Limited Settings - BAIG, WAJEEHA BASHIR; IHSAN, MUHAMMAD; BADICU, GEORGIAN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Esophageal varices are a common and life-threatening complication of liver cirrhosis, particularly in developing countries like Pakistan, where delayed diagnosis and limited access to endoscopic facilities pose significant challenges. Identifying non-invasive predictors can help stratify patients at risk, enabling timely intervention and better resource allocation. Objective: To determine the prevalence of esophageal varices in cirrhotic patients, identify strong clinical and laboratory predictors, and evaluate the utility of non-invasive parameters in guiding screening in resource-limited settings. Methods: This cross-sectional study was conducted at Sir Ganga Ram Hospital, Lahore, from December 2022 to October 2023. A total of 100 patients with clinically and radiologically confirmed liver cirrhosis were included. Demographic, clinical, laboratory, and ultrasound data were recorded. All patients underwent upper gastrointestinal endoscopy to confirm the presence and grade of esophageal varices. The association of non-invasive parameters such as platelet count, splenomegaly, portal vein diameter, Child-Pugh class, and serum albumin—with the presence of varices was analyzed. Results: Out of 100 cirrhotic patients, 71% were found to have esophageal varices. The majority had Grade II (39.4%) and Grade I (31%) varices. Significant associations were observed between the presence of varices and platelet count <100,000/mm³ (69%), splenomegaly (80%), portal vein diameter >13 mm (66%), and serum albumin <3.0 g/dL (60%). Most patients belonged to Child-Pugh class B (44%) or C (32%). Hepatitis C was the leading cause of cirrhosis (58%). Conclusion: Esophageal varices are highly prevalent in Pakistani cirrhotic patients. Easily available non-invasive indicators such as thrombocytopenia, splenomegaly, low albumin, and increased portal vein diameter strongly correlate with the presence of varices. These predictors can guide targeted screening and reduce reliance on endoscopy in resource-limited settings.